2019
DOI: 10.3389/fmars.2019.00526
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Fish Chorus Distributions in Southern California Using an Autonomous Wave Glider

Abstract: Passive acoustics is a tool to monitor behavior, distributions, and biomass of marine invertebrates, fish, and mammals. Typically, fixed passive acoustic monitoring platforms are deployed, using a priori knowledge of the location of the target vocal species. Here, we demonstrate the ability to conduct coastal surveys of fish choruses, spatially mapping their distributions with an autonomous surface vehicle. For this study, we used an autonomous Liquid Robotics Wave Glider SV3 equipped with a Remora-ST underwat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The signals were lower in intensity at the offshore sites than at the inshore sites, which suggested that the chorus propagated from the inshore sites to the offshore sites or that the offshore sites contained fewer fish. Pagniello et al (2019) used a Wave Glider surface vehicle to detect five types of fish choruses along the California coast and stated that the second type of chorus was the same as the 400-800 Hz chorus reported by Reshef et al (2018). In the deep-sea waters off of Australia, several fish choruses were also detected.…”
Section: Introductionmentioning
confidence: 78%
“…The signals were lower in intensity at the offshore sites than at the inshore sites, which suggested that the chorus propagated from the inshore sites to the offshore sites or that the offshore sites contained fewer fish. Pagniello et al (2019) used a Wave Glider surface vehicle to detect five types of fish choruses along the California coast and stated that the second type of chorus was the same as the 400-800 Hz chorus reported by Reshef et al (2018). In the deep-sea waters off of Australia, several fish choruses were also detected.…”
Section: Introductionmentioning
confidence: 78%
“…Afterward, we recorded sounds only in the evenings to save energy (Table 1). Most soniferous fishes are primarily active at night (Luczkovich et al, 2008b;Pagniello et al, 2019) but see Nelson et al (2011). The sound signal was measured from the calibrated hydrophone along the track of the wave glider in each mission.…”
Section: Methodsmentioning
confidence: 99%
“…Traditionally, passive acoustic monitoring has used fixed hydrophones and dataloggers (Rountree et al, 2003;Luczkovich et al, 2008a;Locascio et al, 2012;Rice et al, 2016), but now this monitoring can be done from mobile gliding vehicles (Wall et al, 2012;Greene et al, 2014;Luczkovich et al, 2019;Pagniello et al, 2019). The challenges presented by such platforms include the diurnal and temporally variable nature of the changing soundscape as a glider moves through the sea, which also changes with the glider's geographic position.…”
Section: Introductionmentioning
confidence: 99%
“…Although a relatively recent technology, a number of scientific studies have been cited in the literature that reveal the flexibility of the Wave Glider's capabilities in other oceanographic subdisciplines that range from biological acoustics (Hildebrand et al, 2014;Pagniello et al, 2019), to ocean chemistry (Bresnahan et al, 2016), to seafloor geodesy (Foster et al, 2020). The robust design and autonomous capabilities of this cost-effective measurement platform have also unlocked new opportunities for comparisons between in-situ data and satellite products in remote locations as demonstrated with Chl-a measurements across the Pacific Ocean (Goebel et al, 2014) and wind observations in the Southern Ocean (Schmidt et al, 2017), with similar correlation studies currently underway that focus on better understanding submesoscale ocean dynamics through a comprehensive dataset that includes direct measurements from Wave Gliders as well as airborne observations from cutting edge, remote sensing technologies (see NASA-funded Sub-Mesoscale Ocean Dynamics Experiment, or S-MODE).…”
Section: Introductionmentioning
confidence: 99%